KAJIAN REGULASI BADAN PENGELOLA INVESTASI DANANTARA SEBAGAI UPAYA PENEGAKAN HUKUM PIDANA EKONOMI - Arkaan, Muhammad Naufal; Budi Asri, Dyah Permata (Gapenas Publisher, 2025)
This study aims to evaluate two main aspects of the establishment of the Danantara Investment Management Agency, namely (1) whether its implementation has reflected the initial goal of being a transparent, efficient, and good governance-oriented state investment management institution, and (2) the extent to which Danantara regulations are effective as an instrument for enforcing economic criminal laws against potential irregularities. The juridical – normative research method is used with a qualitative approach, based on the analysis of primary legal documents (Law No. 1 of 2025, Government Regulation No. 10 of 2025) and secondary sources such as journals, expert articles, and international transparency frameworks (Santiago Principles and Temasek practices). The results indicate that although the regulation formally emphasizes the principles of transparency, efficiency, and good governance, its implementation shows significant weaknesses: audits of the BPK and KPK should only be conducted after the approval of the DPR, the management structure dominated by political figures increases the risk of conflicts of interest, and the disclosure of public information is still minimal. On the enforcement side of economic criminal law, regulations provide a framework for audit mechanisms and protection of professional decisions (business judgment rules), but their weaknesses in the aspects of independence and operational supervision reduce the effectiveness of enforcement. Strategic suggestions include strengthening access to independent audits, restructuring management to be professional and non-political, fully enforcing good governance principles, and restricting business judgment rules to remain realistic in accountability.